International case studies in tourism marketing - Aktaş, Gürhan; Kozak, Metin, 1968- (Routledge International Case Studies in Tourism, 2022)
This international case study book provides 27 expertly curated case studies on the topic of tourism marketing, each with detailed implementation instructions for the instructor in order to maximise student participation and learning. The dynamic characteristic of the industry under the influence of micro and macro environment factors requires future professionals to be equipped with appropriate skills and competencies to deal with such factors in real-life practices. Curated and developed by industry experts and practitioners, these case studies embody real-world scenarios with the aim of best preparing students for their future careers. This compelling set of case studies follows a logical and uniform structure and covers topics such as marketing mix, crisis management, digital marketing, quality development, product development and sustainability. With reflective questions throughout to aid both in-class discussion and self-study, this book is an ideal study resource for use in higher and vocational education, and its unique, teaching-led approach positions it as a vital study tool for instructors and students alike.- Resumé vydavatel